Accounting for firm heterogeneity in global value chains - Fortanier, Fabienne; Miao, Guannan; Kolk, Ans; Pisani, Niccolò (Journal of International Business Studies, 2020)
Abstract The growing interest in global value chains (GVCs) has been paired with a greater appreciation of the need for better measurement methods, as reflected by recent initiatives from academia and leading international organizations. This research note focuses on one method to measure GVCs that has been recommended in recent scholarly work, namely input–output models, but goes beyond the industry level of analysis by introducing intra-industry firm heterogeneity. Our illustrative application to multinational enterprises (MNEs) versus domestic firms’ participation in GVCs enhances our understanding of their specific role in GVCs and how such engagement varies across countries and industries. While showing that MNEs’ contribution to value-added exports is considerably smaller than what is suggested by traditional trade statistics, our findings also, interestingly, document that the higher import content of exports of MNEs can go hand in hand with the creation of local backward linkages as a function of their much higher specialization in only parts of the production process vis-à-vis domestic firms. By answering relevant questions on MNEs’ engagement in GVCs that have hitherto been impossible to address comprehensibly and in a cross-country comparative setting, this application illustrates how the methodology has great potential for international business research.